Non-resonant light scattering in dispersions of 2D nanosheets - Harvey, Andrew R.; Backes, Claudia (Nature Communications, 2018)
Quantitative analysis of the extinction spectra of dispersions of 2D materials is complicated by light scattering. Here, the authors investigate non-resonant scattering in suspensions of wide-bandgap nanosheets, and develop a general model which allows the scattering spectra to be used as metrics for particle size in nanosheet dispersions.